A new distributed control strategy to coordinate multiple dstatcoms in LV network - Mokhtari, G.; Nourbakhsh, G.; Zare, Firuz; Ghosh, A. (2013)
Voltage rise is the main issue which limits the capacity of Low Voltage (LV) network to accommodate more Renewable Energy (RE) sources. In addition, voltage drop at peak load period is a significant power quality concern. This paper proposes a new robust voltage support strategy based on distributed coordination of multiple distribution static synchronous compensators (DSTATCOMs). The study focuses on LV networks with PV as the RE source for customers. The proposed approach applied to a typical LV network and its advantages are shown comparing with other voltage control strategies. © 2013 IEEE.